2020
DOI: 10.1002/csr.1932
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Perceived corporate social responsibility and innovative work behavior: The role of employee volunteerism and authenticity

Abstract: Despite the clear importance of perceived corporate social responsibility for employee's innovative work behavior, how and when perceived corporate social responsibility fosters said behavior is not very well understood. Research at the individual level of corporate social responsibility has been growing rapidly. This study proposes that perceived corporate social responsibility has a substantial influence on employee's innovative work behavior and this relationship is mediated by authenticity and volunteerism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 104 publications
3
42
0
3
Order By: Relevance
“…Consequently, the employees also think that they should support their organization by performing extra-roles, one of such behaviors is innovative work behavior. This finding of the current study is in line with several previous researchers [49,[100][101][102][103][104].…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, the employees also think that they should support their organization by performing extra-roles, one of such behaviors is innovative work behavior. This finding of the current study is in line with several previous researchers [49,[100][101][102][103][104].…”
Section: Discussionsupporting
confidence: 94%
“…In an organization where the safety and mental stability of employees are encouraged, it is likely to expect that employees to come up with new and innovative ideas. A plethora of previous research studies establishes that CSR-E is positively related to EIB [ 31 , 53 , 69 , 70 ]. The CSR activities of an organization foster an environment of confidence among the employees and this sense of confidence urges them to take risks and think about innovative ways to induce organizational effectiveness [ 71 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…CSR is an integral part of business strategies and it has a long-lasting impact on the employees to induce their performance [ 30 ]. CSR engagement of an organization promotes fairness and honesty at the workplace and employees believe that their organization will reliability and psychological security, where employees can act without fear of consequences and take risks [ 31 ]. Thus, CSR promotes a work environment that has a significant impact on employees’ innovative capability [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within micro level CSR studies, mostly customers (García de Leaniz & Del Bosque Rodríguez, 2015; González‐Rodríguez & Díaz‐Fernández, 2020; Swimberghe & Wooldridge, 2014; Yin, Du, & Chen, 2020), qualified prospective employees (Boğan & Dedeoğlu, 2019a; Horng, Hsu, & Tsai, 2019), local people (Su et al, 2017; Lee, Kim, & Kim, 2018; Gursoy, Boğan, Dedeoğlu, & Çalışkan, 2019) and incumbent employees' responses to CSR practices are investigated. Extant studies have shown a positive relationship between hospitality employees' CSR perceptions and various employee outcomes such as affective organizational commitment (Wong & Gao, 2014), organizational identification (Cheema, Afsar, Al‐Ghazali, & Maqsoom, 2020; Park & Levy, 2014), employee volunteerism (Afridi et al, 2020), work engagement (Gürlek & Tuna, 2019), job satisfaction (Appiah, 2019; Boğan, Türkay, & Dedeoğlu, 2018), authenticity (Afridi et al, 2020), organizational citizenship behavior (Hur, Moon, & Choi, 2019; Kim, Rhou, Uysal, & Kwon, 2017), trust in organization (Boğan & Dedeoğlu, 2019b) pro‐environmental behavior (Cheema et al, 2020), job crafting (Hur et al, 2019), and innovative work behavior (Afridi et al, 2020). However, it is stated that employees' perceptions of CSR is “still an under‐researched area” in hospitality industry (Ko, Chan, & Wong, 2019, p. 1879).…”
Section: Introductionmentioning
confidence: 99%